Rediscovering Eco-Consciousness: Human-Nature Symbiosis in Richard Powers’ The Overstory - Bhusal, Tilak (Vox Batauli, 2024)
Richard Powers' novel The Overstory delves into the intricate relationship between humans and nature, highlighting the themes of eco-consciousness, struggle, and suffering. This research paper critically analyzes the portrayal of eco-consciousness in the novel, examining how characters' experiences of struggle and suffering contribute to their awakening environmental awareness. Drawing from ecocritical perspectives, this article aims to illuminate the profound implications of eco-consciousness as depicted in the novel. The novel intricately weaves together the lives of various characters, each with their unique and profoundly empathetic connection to trees and the environment, highlighting the struggles and suffering they endure in their pursuit of environmental activism.